Analisis Penerapan Media Prisma Berbasis Augmented Reality dengan Model Knisley pada Materi Prisma Kelas V SD Kuanino 3 Kota Kupang - Bayu Cindi F. Bianome; Kristina E. Noya Nahak; Gracela Natalia Hendrik; Imanuel Ndiy; Volia Hana; Maria D. Hoar (Universitas Cokroaminoto Palopo, 2024)
Learning is a process to help students learn well and where interaction or reciprocal relationships occur between students and their environment in achieving a goal. And to achieve this goal requires media and learning models. One of them is Augmented Reality media with the Knisley learning model. The aim of this research is to find out how to apply Augmented Reality learning media with the Knisley learning model and what the learning outcomes of students are in using Augmented Reality learning media with the Knisley learning model on class V prism material at SD GMIT Kuanino 3, Kupang City. This type of research is quantitative research with a descriptive method. The data collection techniques used in the research are observation, interviews and tests. The observation data is supported by the results of interviews with students and teachers who found that the use of Augmented Reality-based prism media with the Knisley learning model makes learning more enjoyable. Allows students to visualize prisms interactively, supporting active learning. From the test results, it is said that learning outcomes are complete after using augmented reality-based prism media with the Knisley model. So it is said that students fulfill the specified KKTP. This learning not only increases students' understanding, but also improves critical thinking skills and abilities. Thus, the application of prism media based on Augmented Reality with the Knisley model can be considered an innovative and effective approach to prism learning.